Devenir “macho alpha”: performances de seducción heterosexual en una escuela de coaching de la Ciudad de Buenos Aires - Pérez Ripossio, Ramiro Nicolás (El Colegio de México A.C., 2020)
The article characterizes acts of masculine seduction at a coaching school in Buenos Aires in 2019 (March-December) that teaches an approach to heterosexual dating based on bestseller The Game. Penetrating the secret society of pickup artist (2006) and The Mystery Method: How to Get Beautiful Women Into Bed (2007), both of which have had an impact on the “seduction community”. Mainly based in qualitative analysis on ethnographic research method, grounded theory and participant observation. It was found that the school promotes the idea of creating affectional bonds through sexual domination according to a concept of gender based on hegemonic masculinity.